Estudio e implementación de sistema de control para estabilizar frecuencia de fuente de luz láser con respecto a transición atómica del cesio (2020)
Ultrastable laser sources are relevant because of the role they play in the materialization of technologies such as the GPS, quantum computers and atomic clocks, among others. The process of constructing a frequency stabilized laser source in the near infrared, referenced to a cesium atomic transition via Extremum-Seeking Control is discussed in this document. Along this discussion, the development and experimental validation of a computational model that reflects the dynamics of the frequency stabilized laser source is presented. The extremum seeking controller is studied using the developed computational model. This project resulted in a functional frequency stable laser source in the Quantum Optics Laboratory at Universidad de los Andes.